A Cross-Sectional Study on Various Determinants of Tobacco Consumption among Undergraduate Students in Rajkot and Morbi Districts, Gujarat, India, 2016 - Zalak R Matariya; Vaidehi S Gohil; Umed V Patel; Rajan H Upadhyay (Medsci Publications, 2017)
Background: Tobacco is the foremost cause of preventable death in the world and India. Cigarettes kill one in two smokers prematurely, half of these deaths occurring during middle age (mean: 35.69 years). The objective was To study various determinants of tobacco consumption among undergraduate students Methods: A cross-sectional study conducted using self-administered questionnaire among 2000 students during February-March 2016 in 20 colleges of different streams and ratio of male: female was kept 3:1. A self-administered questionnaire was used. Data entry and analysis was done using Microsoft Office Excel 2013 and Epi-Info 7. Results & Conclusion: Prevalence in male was 11.2% for tobacco consumption but in female the prevalence was 0.0%. Family history was present in 87.3% tobacco consumers and it had statistically significant association with tobacco consumption. Conclusion: Tobacco consumption is more common among males. Family history, parent's education and type of native are common factors affecting tobacco consumption. Most common influential factor for initiation of tobacco consumption was friends.